Pelatihan Pemanfaatan Microsoft PowerPoint dan Doratoon bagi Aparatur Desa Ponggang Kabupaten Subang - Rahmah, Mutia; Hartono, Bagus Wahyu; Hamdi, Muchlis; Rahman, Hardiyanto; Saribulan, Nur (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2023)
Human resources play an important role in the process of administering state government, especially at the village level, which directly interacts with the community. This closeness of course requires village officials to have digital skills as a form of communication with the community. These skills are needed when currently government tends to develop towards digital government with an Electronic Based Government System (SPBE). In the midst of this reality, villages and village governments still work in a conventional pattern, namely the pattern of carrying out tasks manually. The aim of this community service activity is to increase the competency of village officials in making presentation materials using Microsoft PowerPoint and Doratoon. This community service activity is carried out using 2 (two) methods, namely training and practice through 4 (four) activity stages including identification, formulation, implementation and evaluation of activities. Training on the use of Microsoft PowerPoint and Doratoon for Ponggang Village officials has been implemented in accordance with the identification and formulation stages. This can also be seen from the evaluation results which show participant satisfaction in receiving the training material and being able to practice the results of the training that was previously delivered. In the future, competency improvement training for Ponggang Village officials is expected to be more varied and carried out on an ongoing basis.